Normalizing eye-tracking metrics: Correcting area bias in visual attention studies - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Jéssica Sousa Guimarães; André Pimenta Freire; Cleiton Antonio Nunes; Ana Carla Marques Pinheiro (Food Quality and Preference, 2026)

Sublethal toxicity of selenium nanoparticles in zebrafish early life stages: biochemical and behavioral responses - Pearl Ofoegbu; Rita Duarte; Soraia Almeida; Alexandre Marques; David Daniel; Luís Barros; Ricardo J. B. Pinto; Victor Galhano; Bruno Nunes (Environmental Science and Pollution Research, 2026)

The Missing Branches of the Bee Tree of Life: Addressing Global Darwinian Shortfalls and Their Drivers - Felipe Walter Pereira; Matheus Lima Araujo; Anderson Lepeco; Bruno Ferreira Marques; Hugo Bampi; Lucas Jardim; Luísa Vareira; Luisa G. Carvalheiro; Thiago F. Rangel; José Alexandre F. Diniz Filho (Journal of Biogeography, 2026)
Aim Estimate the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships) of bees worldwide, as well as identify their drivers. Location Global. Taxon Bees (Hymenoptera, Anthophila). Methods We built phylogenies for over 12,000 bee species, combining the most comprehensive phylogeny and an algorithm with random solutions to insert missing lineages. The Darwinian shortfall was quantified as the Phylogenetic Diversity (PD) deficit, the ratio of inserted branch lengths at the assemblage level. We identified potential ecological and socioeconomic drivers of the Darwinian shortfall using Simultaneous Autoregressive (SAR) models. Results The highest shortfalls were identified in the Southern Hemisphere. Mean species range size and species richness were the strongest drivers, as smaller ranges and higher richness were associated with higher deficits. Per capita GDP was negatively associated with PD deficits, while population and road densities showed positive but weak effects. Sample completeness had a weaker effect, limited by missing occurrence data in many regions. Main Conclusions Our findings underscore the need for integrative efforts combining taxonomy, data digitization, adequate research investments, and targeted sampling, especially in the Global South. Overcoming the Darwinian shortfall is essential to develop robust strategies to preserve the Tree of Life, especially for one of the most important groups of pollinators while facing the ongoing biodiversity crisis.

Potato starch as a bio-based admixture in cement mortars - Pablo Pacceli Silva Braz; Pietra Maria Marques Braga; Leonardo Carvalho Mesquita; Marília Gonçalves Marques; José Alexandre Tostes Linhares Junior; Afonso Rangel Garcez de Azevedo; Markssuel Teixeira Marvila (Journal of Environmental Management, 2026)

El Niño Reduces Beta Diversity of Fish Assemblages Across a Large Subtropical Coastal Lagoon - Yan Gonçalves Gowert; Rafael Lima Oliveira; Fabiano Correa; Thiago dos Santos Tuchtenhagen; Marcelo Bassols Raseira; Valéria Marques Lemos; Alice Marlene Grimm; Alexandre Miranda Garcia (Estuaries and Coasts, 2026)
The El Niño –Southern Oscillation (ENSO) profoundly alters climatological and hydrological conditions, reshaping environmental gradients and ecological dynamics in riverine, estuarine, and coastal ecosystems. We hypothesized that El Niño events would promote homogenization of fish assemblages and reduce β-diversity, whereas La Niña conditions would enhance habitat differentiation and increase β-diversity. To test this hypothesis, we investigated variations in fish β-diversity across a freshwater–estuarine–marine gradient in the Patos Lagoon, southern Brazil, under La Niña , El Niño , and neutral climatic conditions. We analyzed total β-diversity and its local and species contribution components in relation to environmental variability associated with ENSO phases. The results revealed a clear pattern of homogenization between the estuarine and marine environments during El Niño , characterized by increased species sharing and reduced taxonomic differentiation. Species sharing between these regions increased from 10 to 13 species during La Niña and neutral conditions, respectively, to 18 species during El Niño . In contrast, La Niña promoted stronger habitat compartmentalization, resulting in higher total β-diversity (0.558) than El Niño (0.538) and neutral conditions (0.528), indicating greater spatial heterogeneity in fish assemblages. These findings support our hypothesis that ENSO-driven changes in environmental gradients shape fish β-diversity, with El Niño promoting biotic homogenization and La Niña enhancing habitat differentiation. As ENSO events are projected to become more frequent and intense, these processes may have important implications for the biodiversity and structural organization of subtropical coastal lagoons and other estuarine ecosystems.

Agroforestry systems as habitat aggregators: a spatiotemporal analysis of the Brazilian subtropical Atlantic forest - Bruno Barbosa Silva; Diego Brum; Alexandre Copatti Loregian; Leonardo Marques Urruth; Alexandro Marques Tozetti (Agroforestry Systems, 2026)
Agricultural expansion, especially in the Neotropics, has been a major driver of habitat and ecosystem loss through the conversion of native vegetation into croplands and pastures. In southern Brazil, large areas of Atlantic Forest have been lost for this purpose. Current estimates suggest that only 7.5% of the original Atlantic Forest remains. In contrast, alternative agricultural approaches, particularly Agroforestry Systems (AF), have emerged as sustainable strategies that mitigate negative impacts on natural ecosystems. We analyzed the relationship between AF and the land use pattern in Atlantic Forest of southern Brazil, based on satellite images obtained between 2000 and 2020. We evaluated the changes in land use around the AF and compared them with random units (RU). From 2000 to 2020, areas surrounding AF tend to remain stable, showing no evident reduction in native habitats such as forests. In contrast, areas around RU exhibited a marked expansion of agriculture and pasture cover. This suggests that AF contribute to the conservation of Atlantic Forest in Southern Brazil.

Evaluation of ceramic and polymeric membranes for crossflow microfiltration of coconut water: Filtration performance and composition of the clarified coconut water - José Diogo da Rocha Viana; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Carlos Alberto Kenji Taniguchi; Arthur Claudio Rodrigues de Souza; Fernando Antônio Pinto de Abreu; José Carlos Cunha Petrus; Kirley Marques Canuto (Journal of Food Engineering, 2026)

Nursery habitat use of juvenile meagre (Argyrosomus regius): findings from acoustic telemetry in the Tagus estuary - João P. Marques; Pedro R. Almeida; Nuno Prista; José Lino Costa; Carlos M. Alexandre; Catarina S. Mateus; Isabel Domingos; Patrick Reis-Santos; Bernardo R. Quintella (Marine Biology, 2026)
We used acoustic telemetry to investigate the nursery habitat use of 33 juvenile meagre Argyrosomus regius (mean size = 581 ± 105.1 mm), recording more than 60,000 detections in the Tagus estuary, located in the North-Eastern Atlantic. All individuals used the nursery area from spring to autumn, and a small number (22.2%) remained in the Tagus estuary during winter. Daily movements averaged 6.2 ± 1.9 km, with maximum daily distances reaching 41.2 ± 17.3 km. Peak movement activity was observed in July-October (average distance = 367.3 ± 240.3 km), and predominantly during the night. Furthermore, larger sized individuals returned to the Tagus estuary in subsequent years, typically using this habitat from May to October for an average of 108.5 ± 43.0 days. Spatial analyses indicated that the lower and middle sections of the Tagus estuary serve as important nursery habitats year-round, whereas the upper estuary functions as a nursery primarily from March through June. Network movement analyses highlighted that specific areas in the middle and lower reaches exhibit higher movement activity. Generalized additive modelling indicated that the occurrence of juvenile meagre in the Tagus estuary was significantly influenced by temporal and environmental variables, including day of the year, salinity, dissolved oxygen, and temperature, measured both in the estuary and in the adjacent coastal area. These findings enhance our understanding of the habitat use in estuarine nursery areas and emphasise the importance of incorporating targeted fisheries management strategies in nursery areas to promote the sustainability of this ecologically and economically important fish.

Machine learning-based stratification of chagas heart failure severity using ECG power spectral biomarkers - Pedro Ribeiro; João Alexandre Lobo Marques; Maria Inês Barbosa; Roberto C. Pedrosa; João Paulo do Vale Madeiro; Pedro Miguel Rodrigues (Medical & Biological Engineering & Computing, 2026)

Ecological risk assessment of dredged sediments from a tropical urban lagoon: Is Brazilian law sufficient for protecting aquatic and soil biota? - Gustavo Koifman; Ricardo Cesar; Domynique Santos; Yan Ribeiro; Lara Filgueira; Pedro Lavinas; Danielle Soares; Rodrigo Lourenço; André Salomão; Marcia Marques; Katia Alexandre; Manuel Carneiro; et al. (Anthropocene, 2026)

Geochemistry, U-Pb and Sm-Nd isotopic constraints on Rhyacian metamafic-metaultramafic plutonic rocks in the southern São Francisco paleocontinent, Mineiro belt, Brazil: petrogenesis and tectonic implications - Marco Aurélio Piacentini Pinheiro; Ciro Alexandre Ávila; Joana Reis Magalhães; Catarina Labouré Benfica Toledo; Márcio Antônio Silva; Everton Marques Bongiolo; Francisco Teixeira Vilela; Mahyra Tedeschi; George Luiz Luvizotto; Wilson Teixeira (International Geology Review, 2026)

Influence of coral reef morphology on wave climate and sea-level rise projections along a reef-protected beach in Northeast Brazil - Larissa Fernandes de Lavor; Maria Cecilia Silva Souza; Karina Massei; Alexandre dos Santos Souza; Valdir do Amaral Vaz Manso; Virgínio Henrique de Miranda Lopes Neumann; Pedro Costa Guedes Vianna; Christianne Maria da Silva Moura; Nadja Cecília de Freitas Silva; Richarde Marques da Silva; Rogério dos Santos Ferreira; Jefferson da Costa Silva; et al. (Regional Studies in Marine Science, 2026)

Emerging Bacterial Resistance and Genotoxicity of Water-Soluble Fractions of Agricultural Soils from the Semiarid Region of Brazil Affected by the Continuous Use of Glyphosate - Karolayne Silva Souza; Amanda Alves de Araujo; Milena Roberta Freire da Silva; Kátia Cilene da Silva Felix; Kaline Catiely Campos Silva; Ricardo Marques Nogueira Filho; Lívia Caroline Alexandre de Araujo; Amanda Vieira de Barros; Fabricio Motteran; Elvis Joacir De França; Claudia Rohde; Maria Betânia Melo de Oliveira (Bulletin of Environmental Contamination and Toxicology, 2026)
The use of herbicides in modern agriculture has been the subject of ongoing debate due to their negative impacts on the environment and human health. The aim of this study was to assess the bacterial, physicochemical and genotoxicity parameters of three soil samples of public farming settlements in Petrolândia, Brazil. The bacterial resistance patterns were examined after soil exposures to a known concentration of glyphosate (2.5%). Genotoxicity was assessed through the Drosophila melanogaster Comet assay, exposed to water-soluble fraction (WSF) soil samples, followed by the quantification of seven chemical elements. The results indicated that, although physicochemical parameters remained within acceptable limits, there was a significant presence of resistant bacteria, particularly Stenotrophomonas maltophilia , Bacillus cereus and Enterobacter cloacae . Comet assay results (Damage Index and Damage Frequency) presented a significant level of genotoxicity in two of the three WSFs. Clustering analysis associated the genetic damage to the presence of chrome and zinc heavy metals. The predominance of multidrug-resistant bacteria, combined with levels of genotoxicity, suggests that these soils exposed to glyphosate contamination represents a risk to the sustainability of Brazilian semiarid agriculture.

What percentage of neuromuscular strength reduction in older adults determines the decline in walking speed? - Yasmin Oliveira Machado; Mariane Marques Luiz; Roberta de Oliveira Máximo; Sara Souza Lima; Andrew Steptoe; Cesar de Oliveira; Tiago da Silva Alexandre (GeroScience, 2026)
Background/Objective Although different neuromuscular strength (NS) cutoff points have been proposed to identify low walking speed (WS) in older adults, the extent to which NS changes predict long-term WS decline remains unclear. This study aimed to determine the percentage of NS change associated with WS decline in older adults. Methods A longitudinal analysis was conducted using data from 4,541 participants aged ≥ 60 years in the ELSA Study. Changes in NS over four, eight, and twelve years of follow-up, compared to baseline, were categorised into nine groups: maintenance of NS within ± 5%, increases of 5–10%, 10–15%, 15–20%, or more than 20%, and reductions in the same ranges. Generalised linear mixed models were used to evaluate WS trajectories (m/s) as a function of NS changes, adjusted for sociodemographic, behavioural, and clinical factors. Results Participants who experienced a 15–20% (-0.007 m/s per year; 95% CI: -0.013 to -0.002) and more than 20% (-0.004 m/s per year; 95% CI: -0.007 to -0.001) reduction in NS had greater WS decline compared to those with stable NS (± 5%). Over 12 years, these reductions corresponded to WS declines of -0.189 m/s and -0.144 m/s, respectively. Conclusion Losing 15% or more of neuromuscular strength reduces walking speed over time. Therefore, monitoring the percentage change in NS can serve as a useful tool for early detection of the risk of WS decline, allowing for more personalised clinical investigations and timely neuromuscular strengthening interventions to minimise adverse effects on mobility in older adults. Graphical Abstract

Sex-dependent behavioral and hypothalamic receptor changes after early-life monosodium glutamate (MSG) exposure and adult social stress in Wistar rats - Juliano Ten Kathen Jung; Luiza Souza Marques; Carlos Alexandre Brambila; Fabíola Caldeira dos Santos; Cristina Wayne Nogueira (Metabolic Brain Disease, 2026)

Semi-synthesis of sodium copper chlorophyllin from Chlorella vulgaris cultivated under continuous photoperiod and sequential extraction of fatty acids and exopolysaccharides - Jamila Sueira de Jesus Silva; Fábio Alexandre Chinalia; Carolina Oliveira de Souza; Denilson de Jesus Assis; Jania Betânia Alves da Silva; Gabriele Marques dos Santos; Fernanda Teixeira Cruz; Ravena Maria de Almeida Medeiros; Paulo Vitor França Lemos; Lucas Guimarães Cardoso (Food and Bioproducts Processing, 2026)

Removal of Bisphenol A, Bisphenol S, and Estrogenic Activity from Real Wastewater Using a Multi-stage IFAS System - Amanda F. do Amaral; Alexandre S. A. da Silva; Deivisson L. Cunha; Priscila M. de O. M. Cunha; Rodrigo Coutinho; Marcia Marques (Bulletin of Environmental Contamination and Toxicology, 2026)
This study evaluated the removal of bisphenol A (BPA), bisphenol S (BPS), and estrogenic activity from real municipal wastewater using a pilot-scale multi-stage integrated fixed-film activated sludge (MS-IFAS) system. The configuration comprised five sequential reactors (Anaerobic, Anoxic-1, Aerobic under IFAS, Anoxic-2, and Re-aeration) providing distinct redox conditions. Influent concentrations averaged 112.6 ± 49.5 µg L −1 for BPA and 6.6 ± 3.0 µg L −1 for BPS. Overall removal efficiencies reached 99.8 ± 0.1% and 97.7 ± 1.0%, respectively, despite influent variability. The aerobic IFAS reactor was the main contributor to contaminant degradation, maintaining performance even after a > 90% biomass loss. Estrogenicity, assessed by the Yeast Estrogen Screen assay and expressed as 17β-estradiol equivalents (E2-EQ) decreased by 83.2% (0.031–0.005 ng L −1 ). Effluent E2-EQ values were below ecotoxicological thresholds, indicating negligible estrogenic risk to aquatic organisms. These highlight the strong potential of MS-IFAS for removal of xenoestrogenic contaminants in real wastewater.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Reply to Figueroa‐Muñoz et al.'s comment on ‘multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha (Walbaum, 1792) (Salmonidae) in the world's largest chocked coastal lagoon’ - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Cost-Effective rhamnolipids production from corn Bran and their application in essential oil extraction - Juliana P. Marques Teixeira; Gabriela Dornelas Marques; Michel Pedro Batista; Karen Stefany Conceição; Thaísa Maria da Roda Lino; Natalia Belebecha Terezo; Cesar Augusto Tischer; Alexandre Orsato; Gerson Nakazato; Nicole Caldas Pan; Josiane A. Vignoli; Doumit Camilios-Neto (World Journal of Microbiology and Biotechnology, 2026)

Enhancing productivity in growing rabbits: the impact of lipid source supplementation - Alexander Alexandre de Almeida; Jean Kaique Valentim; Joyce Zanella; Orlando Filipe Costa Marques; Janaina Tayna Silva; Leonardo da Silva Fonseca; Andrea Maria de Araújo Gabriel; Euclides Reuter de Oliveira (Tropical Animal Health and Production, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Natural deep eutectic systems-based Ginkgo biloba extracts: A natural and sustainable solution for skin care - Marta Marques; Ana Rita Jesus; Ana Rita C. Duarte; Alexandre Paiva (Sustainable Chemistry and Pharmacy, 2025)

An Integrated assessment of naturally occurring radionuclides in a coastal tropical shrimp farm ecosystem: Environmental distribution and potential implications - Jade Guimarães Gomes dos Santos; Rafael Reis Cabral; José Marques Lopes; Gisele Mara Hadlich; Alexandre Barreto Costa; Maria do Rosário Zucchi (Regional Studies in Marine Science, 2025)

Environmental filtering and management effects on functional and taxonomic reef fish diversity in the Abrolhos Reefs, Brazil - Ramón Hernández-Andreu; Fabiana Cézar Félix-Hackradt; Sara Buttrose Kennedy; Jessyca Luana Silva Texeira; Inajara Marques Bezerra; Rodrigo Leão Moura; Alexandre Schiavetti; Carlos Werner Hackradt (Marine Environmental Research, 2025)

Multiple tools to investigate the origin of the exotic species Chinook salmon Oncorhynchus tshawytscha ( W albaum, 1792) ( S almonidae) in the world's largest chocked coastal lagoon - Yan Gonçalves Gowert; Valéria Marques Lemos; Fabiano Corrêa; Sabrina Vollrath; João Paes Vieira; Mario Vinicius Condini; Rodrigo Ferreira Bastos; Mylla Carla Cescon Freire; Ana Paula Cazerta Farro; Antonio Sergio Varela Junior; Cristiano Albuquerque; Maurício Hostim‐Silva; et al. (Journal of Fish Biology, 2025)
Salmonid species have increasingly been established in South America for aquaculture and recreational fishing purposes. This study provides the first scientific record of the Chinook salmon ( Oncorhynchus tshawytscha ) in the Patos Lagoon (32°S), the world's largest choked coastal lagoon. The specimen was a female with 770 mm (total length), 3992.1 g, estimated age of 6 years and an advanced sexual maturation stage. Based on multiple tools (DNA barcoding, stable isotopes in eye lens, otolith growth layers and egg's histological analysis), we discussed potential entry routes for this species into the lagoon.

Ecological diversity and distribution of Penaeoidea shrimps near islands with distinct environmental characteristics on the Northern Coast of São Paulo, Brazil - Alexandre de Oliveira Marques; Paulo Victor do Nascimento Araújo; Carlos Eduardo Rocha Duarte Alencar; Vivian Fransozo; Gustavo Monteiro Teixeira; Fúlvio Aurélio de Morais Freire; Rogério Caetano da Costa (Hydrobiologia, 2025)

Single-dose recombinant FSH as a viable alternative to multi-dose porcine FSH in commercial superovulation protocols in cows - Monique Mazzarollo Frata; Wagner Marques de Lima; Monique Tomazele Rovani; Rogério Ferreira; Alexandre Hênryli de Souza; Rafael Gianella Mondadori; Paulo Bayard Dias Gonçalves; Vilceu Bordignon; Bernardo Garziera Gasperin (Theriogenology, 2025)

Contamination status and evaluation of metal pollution indexes in sediments from shrimp farming in the Lower São Francisco River region, Northeast Brazil - Larissa Santos Xavier; Joel Marques da Silva; Andrielle dos Santos de Jesus; João Batista Pereira; Amanda Silva de Jesus; Marcos Vinicius Teles Gomes; Sarah Adriana Rocha Soares; Andrea Novelli; Elisângela Andrade Passos; Rennan Geovanny Oliveira Araujo; Carlos Alexandre Borges Garcia; Felipo Obed Correia; et al. (Journal of Soils and Sediments, 2025)

Digestive anatomy and diet of free-ranging maned wolf (Chrysocyon brachyurus) - Bruno Costa Silva; Luan Alexander de Oliveira; Marcus Clauss; Claudia Guimarães Costa; Leandro de Oliveira Marques Alexandre; María J. Duque-Correa (Mammalian Biology, 2025)
The maned wolf ( Chrysocyon brachyurus ) is the largest of the currently extant ten species of South American canids and is a monotypic taxon in the genus Chrysocyon , currently classified as Near Threatened by the IUCN. Here we report the anatomy of the gastrointestinal tract (GIT) of 12 free-ranging maned wolves (10 adults, six females, four males, and two juvenile males), nutritional analyses of the gastrointestinal tract (stomach, small, and large intestine) of eight individuals (six females and two males), and the macroscopical examination of the stomach contents of eight individuals (four adult females, two adult males, and two juvenile males). The general anatomy and the dimensions of the maned wolf`s GIT resembled that of other canids. The results of the dietary analyses reported in this study are similar to previously reported data for the species, confirming its omnivorous nature. Vertebrates were found in all stomachs, representing 42.5% of the total dietary mass. Vegetable material was also present in all stomachs, accounting for half of the total dietary mass (50.5%). Anthropogenic material, including cooked rice, glass, and ceramic fragments, were retrieved from the stomach of one individual; such opportunistic feeding behavior has been previously reported. When compared to other Carnivora species classified as omnivores, including the red fox ( Vulpes vulpes ) and the raccoon dog ( Nyctereutes procyonides ), these ‘omnivorous’ carnivores ingest distinctively higher levels of fiber compared to purely faunivorous Carnivora. This information might be important for feeding these species in ex-situ settings.

Trace metal chemical fractionation in airborne particulate matter from a tropical urban area in Brazil - Silvânio Silvério Lopes Costa; Jeferson Cavalcante Alves; Erivaldo Vieira da Silva; Joel Marques da Silva; Larissa Santos Xavier; Vaniele Souza Ribeiro; Dayara Virgínia Lino Ávila; Sidnei Oliveira Souza; Carlos Alexandre Borges Garcia; Gisele Olímpio da Rocha; Rennan Geovanny Oliveira Araujo (Environmental Science and Pollution Research, 2025)

Vitamin D deficiency as a risk factor for cognitive decline in individuals aged 50 or older - Natália Cochar-Soares; Thaís Barros Pereira da Silva; Mariane Marques Luiz; Patricia Silva Tofani; Maicon Luis Bicigo Delinocente; Roberta de Oliveira Máximo; Andrew Steptoe; Cesar de Oliveira; Tiago da Silva Alexandre (GeroScience, 2025)

Correction: First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

First Transcriptome Analysis of Hepatoblastoma in Brazil: Unraveling the Pivotal Role of Noncoding RNAs and Metabolic Pathways - Talita Ferreira Marques Aguiar; Maria Prates Rivas; Edson Mario de Andrade Silva; Sara Ferreira Pires; Gustavo Dib Dangoni; Taiany Curdulino Macedo; Alexandre Defelicibus; Bruna Durães de Figueiredo Barros; Estela Novak; Lilian Maria Cristofani; Vicente Odone; Monica Cypriano; et al. (Biochemical Genetics, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Reverse flotation of iron ore by a new ternary collector-frother reagent: Applications through flotation experiments - Michelle Lacerda Sales Marques; Lucas Andrade Silva; Letícia Maia Prates; Alexandre Moni Pereira; Julio Cesar Guedes Correia; Inna V. Filippova; Lev O. Filippov (Minerals Engineering, 2025)

Treatment with cyclosporine attenuates the inflammatory process and severity of bisphosphonate-induced osteonecrosis of the jaws in rats - Camila Costa Dias; Caio Ferreira Freire Caetano; Gabriella Alves Julião Costa; Antônio Alexandre Coelho; José Vitor Mota Lemos; Dayrine Silveira de Paula; Juliana Paiva Marques Lima; Paulo Goberlânio de Barros Silva (Inflammopharmacology, 2025)

Temporal trends in estuarine-resident fishes: Functional traits and responses to environmental and climatic variability - Nuno Mussá M.U. Escamade; Valeria Marques Lemos; Alexandre Miranda Garcia (Marine Environmental Research, 2025)

NMR-based metabolomics and pathway analysis of leaves and fruits of Cucumis melo L. cultivated under saline stress conditions - Beatriz de Abreu Araújo; Lorena Mara Alexandre Silva; Kirley Marques Canuto; Elenilson Godoy Alves Filho; Karine Silva Pimentel; Rita de Cassia Silva Carvalho; Marlos Alves Bezerra (Food Research International, 2025)

Analysis of germination and vigor of cashew seeds for germplasm conservation by NMR and uPLC-qTOF-MS/MS based metabolomics - Elenilson Godoy Alves Filho; João Ravelly Alves de Queirós; Oriel Herrera Bonilla; Hilton César Rodrigues Magalhães; Edy Sousa de Brito; Paulo Riceli Vasconcelos Ribeiro; Kirley Marques Canuto; Lorena Mara Alexandre e Silva; Ana Cecília Ribeiro de Castro (Food Research International, 2025)

Modulation of Eimeria spp. parasite load on productivity parameters in lambs fed with babassu byproduct - Sara Silva Reis; Henrique Nunes Parente; Anderson de Moura Zanine; Gisele Thamires Araújo da Silveira; Edegleicia Alves de Sousa; Arlan Araújo Rodrigues; Thalia Caldas da Silva; José Gracione do Nascimento Souza Filho; Janaina Marques do Nascimento; Thiago Vinicius Costa Nascimento; Michelle de Oliveira Maia Parente; Carlos Rodrigo Hermosilla; et al. (Tropical Animal Health and Production, 2025)

Multivariate statistical analysis of surface water quality in the capibaribe river (Pernambuco state, Northeast Brazil): Contributions to water management - Jaqueline dos Santos Silva; Livia Caroline Alexandre de Araújo; Milena Danda Vasconcelos; Iago José Santos da Silva; Fabricio Motteran; Rosner Henrique Alves Rodrigues; Carina Lucena Mendes-Marques; Rayanna Barroso de Oliveira Alves; Hernande Pereira da Silva; Maria Paloma Barros; Sivoneide Maria da Silva; Guilherme Malafaia; et al. (Marine Environmental Research, 2025)

Evaluation of Aerosol Optical Depth (AOD) estimated by Copernicus Atmosphere Monitoring Service (CAMS) in Brazil - Altemar Lopes Pedreira Júnior; Leone Francisco Amorim Curado; Rafael da Silva Palácios; Luiz Octávio Fabricio dos Santos; Carlos Alexandre Santos Querino; Juliane Kayse Albuquerque da Silva Querino; Thiago Rangel Rodrigues; João Basso Marques (Theoretical and Applied Climatology, 2025)

Phaseolus lunatus landraces from northeast Brazil: genetic diversity and anthracnose resistance - Vanessa Fernandes Soares; Glauber Santos Pereira; Alexandre de Oliveira Marques; Gildemberg Amorim Leal Junior (Genetic Resources and Crop Evolution, 2025)

Evaluation of metals in surface sediments from shrimp farming areas in the estuarine region of the Baixo São Francisco, in Northeastern Brazil - Larissa Santos Xavier; Raynne Aparecida de Sousa Pires; Marcos Vinicius Teles Gomes; Elisângela Andrade Passos; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Felipo Obed Correia; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Evaluation of shrimp farming impacts on the water quality of the Lower São Francisco watershed region, Brazil - Rômulo André Santos Silva; Gustavo Andrade Araujo Oliveira; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Marcos Vinicius Teles Gomes; Adnívia Santos Costa Monteiro; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Salivary proteins modulate Candida albicans virulence and may prevent oropharingeal candidiasis - Jose Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Brayan Leonardo Bayona-Pacheco; Daniel Clemente de Moraes; Maristela Barbosa Portela; Antônio Ferreira-Pereira; Camila Marques Adade; Thaïs Souto-Padrón; Rosangela Maria de Araújo Soares (Brazilian Journal of Microbiology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Smart hotspot detection using geospatial artificial intelligence: A machine learning approach to reduce flood risk - Seyed MHS Rezvani; Alexandre Gonçalves; Maria João Falcão Silva; Nuno Marques de Almeida (Sustainable Cities and Society, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The impact of plant-based product denomination on consumer expectations and sensory perception: A study with vegan chocolate dessert - Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Louise Paiva Passos; Maria Laura Silva Galdino; Júlia Fernanda Urbano Marinho; Juliana Santos Marques; Karen Lendengue de Matos Regalado; Ana Carla Marques Pinheiro (Food Research International, 2024)

An oblique transpressive soft-collision records the amalgamation of the Siderian-Orosirian Mineiro belt (Brazil) and the São Francisco paleo-craton (Kenorland Supercontinent): Insights from the Bom Sucesso metasedimentary sequence - Alvaro Balmant Pessamilio; Everton Marques Bongiolo; Ciro Alexandre Ávila; Gustavo Luiz Campos Pires; Bianca Saraiva Borges; Elson Paiva Oliveira; Reiner Neumann (Journal of South American Earth Sciences, 2024)

Temporal dominance of Sensations: Do different concepts of “dominance” affect the results? - Katiúcia Alves Amorim; Louise Paiva Passos; Alexandre Henrique Silas Souza; Vinícius dos Santos Cardoso; Rita de Cássia Vieira; Milene de Souza Campos; Jéssica Ferreira Rodrigues; Cleiton Antônio Nunes; Ana Carla Marques Pinheiro (Food Research International, 2024)

Comparison of α and β-acid isomerization in hops and beer using HPLC, confocal microscopy, spectrofluorimetry and chemical analysis of metabolites and essential oils in flowers of different hop cultivars produced in Brazil - Francisco Mateus Gomes do Nascimento; Maria Teresa Salles Trevisan; Manoel Lourenço Alves Neto; Robert Wyn Owen; Edy Sousa de Brito; Lorena Mara Alexandre e Silva; Késya Amanda Dantas Rocha; Carlos Lenz Cesar; Hernandes Faustino de Carvalho; Vitor Bianchin Pelegati; Sthefanny Alves da Silva; Samuel Pedro Dantas Marques (Food Chemistry, 2024)

Neoproterozoic tectonothermal overprint on the Southern São Francisco Craton basement, Brazil - Everton Marques Bongiolo; Christophe Renac; Ciro Alexandre Ávila; Sylvain Gallet; Reiner Neumann (Precambrian Research, 2024)

Association of emojis to the five basic tastes (sweet, salty, sour, bitter and umami) - Lenízy Cristina Reis Rocha; Louise Paiva Passos; Alexandre Henrique Silas Souza; Katiúcia Alves Amorim; Jéssica Ferreira Rodrigues; Ana Carla Marques Pinheiro (Food Quality and Preference, 2024)

Perovskite-type strontium ferrite-based catalyst: Characterization and antibiotic degradation approach - Afonso Henrique da Silva Júnior; Carlos Rafael Silva de Oliveira; Leandro Pellenz; Paulo Alexandre Durant Moraes; Willbrynner Pereira Marques; Luciana Prazeres Mazur; Thiago Guimarães Costa; Adolfo Horn Jr; Selene Maria de Arruda Guelli Ulson de Souza; Antônio Augusto Ulson de Souza; Luciano da Silva; Adriano da Silva (Process Safety and Environmental Protection, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Evaluation of Extraction Methods to Detect Noroviruses in Ready-to-Eat Raw Milk Minas Artisanal Cheese - Carina Pacheco Cantelli; Marcio Roberto Silva; Laís Marques Pimenta; Guilherme Caetano Lanzieri Tavares; Gabriel Assad Baduy; André Almeida Santos Duch; Liliane Denize Miranda Menezes; Alexandre Madi Fialho; Adriana Gonçalves Maranhão; Tulio Machado Fumian; Marize Pereira Miagostovich; José Paulo Gagliardi Leite (Food and Environmental Virology, 2024)

Prevalence of cagA, cagM, vacA and oipA genes in isolates of Helicobacter pylori obtained from hospital patients in Northeast Brazil - Thaynara Millena de Oliveira Bezerra; Keyla Vitória Marques Xavier; Ana Carolina de Oliveira Luz; Isabella Macário Ferro Cavalcanti; Carlos Alexandre Antunes de Brito; Tereza Cristina Leal- Balbino (Brazilian Journal of Microbiology, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Are CAM bromeliad seedlings from Campo Rupestre more tolerant to heat than C3? - Alexandre Aparecido Duarte; Tiago Vilas-Boas; Andréa Rodrigues Marques; José Pires de Lemos-Filho (Theoretical and Experimental Plant Physiology, 2024)

Acaricidal activity of synthetic spilanthol derivative against ticks of medical and veterinary importance - Luis Adriano Anholeto; Guilherme Andrade Brancaglion; Danilo Martins dos Santos; Rafaela Tami Ikeda Kapritchkoff; Karina Neoob de Carvalho Castro; Kirley Marques Canuto; Rodney Alexandre Ferreira Rodrigues; Daniel Souza Correa; Ana Carolina de Souza Chagas; Julio Cezar Pastre (Veterinary Parasitology, 2024)

Opportunistic pathogenicity observed for the endophytic fungus Diaporthe ueckerae on Gossypium hirsutum plants - Matheus Mendonça de Souza Marques; Isabella de Oliveira Silva; Layara Alexandre Bessa; Luciana Cristina Vitorino (Journal of Plant Pathology, 2024)
Cotton crops are routinely threatened by emerging fungal diseases. Fungal endophytes also can be considered latent phytopathogens. In this study we tested the hypothesis that an endophytic strain of Diaporthe , isolated from chlorotic leaves of cotton ( Gossypium hirsutum ), could trigger physiological effects of biotic stress in this oilseed plant. We also assessed the histopathological aspects of the mycelial interaction of the endophyte with the adaxial surface of G. hirsutum leaves. Thus, we studied the synthesis of photosynthetic pigments, pattern of gas exchange, and photochemistry of cotton plants subjected to inoculation with Diaporthe ueckerae via root and leaf at three different phenological stages (vegetative, reproductive, and maturation). Additionally, we histopathologically analyzed infected leaves using electron microscopy to study the process of leaf colonization by this endophytic fungus. We evidenced that D. ueckerae inoculation negatively affected the synthesis of photosynthetic pigments in plants at vegetative and reproductive stages. Moreover, inoculation also negatively affected the photosynthetic rate and carboxylation efficiency of these plants. We also found that the presence of the endophyte increased transpiration and decreased water use efficiency in the plants. Furthermore, foliar inoculation negatively affected stomatal conductance, whereas inoculation via leaf or root reduced the photochemical performance of cotton. We also observed that D. ueckerae colonizes the leaf tissues of G. hirsutum via glandular trichomes and forces penetration into the epidermis using appressoria, and the plant responds by closing the stomata. The observed physiological alterations are indicative of biotic stress, confirming the hypothesis that D. ueckerae may be an opportunistic phytopathogen for cotton plants.

Leaf physiology and histopathology of the interaction between the opportunistic phytopathogen Fusarium equiseti and Gossypium hirsutum plants - Matheus Mendonça de Souza Marques; Luciana Cristina Vitorino; Márcio Rosa; Bruno Matheus Mendes Dário; Fabiano Guimarães Silva; Layara Alexandre Bessa (European Journal of Plant Pathology, 2024)
Fungal diseases constitute a major challenge in the cultivation of the world's most important textile plant, cotton. Opportunistic fungi attack plants and promote physiological alterations and tissue damage, thereby causing losses in productivity. Herein, the hypothesis that Gossypium hirsutum L. plants are physiologically affected, depending on the phenological stage and site of infection (root system or leaf), when affected by the opportunistic phytopathogen Fusarium equiseti was tested. To this end, the photosynthetic pigment production, gas exchange, chlorophyll a fluorescence, and histopathological mechanisms involved in the plant-phytopathogen interaction were evaluated. This study aimed to diagnose the most aggressive route of infection by comparing infection via root with infection via the leaf, and to identify the developmental stage with the highest susceptibility by comparing different phenological stages. Cotton plants show metabolic losses at the maturation stage, resulting in low photosynthetic pigment concentrations, low photosynthetic rates, and photochemical stress. However, when infected by F. equiseti in the root region, the photosynthesis and photochemistry of these plants are more affected than plants inoculated in the leaf region. Low net photosynthesis ( A ) and water use efficiency ( WUE ) rates, but high light absorption flux (ABS/RC) and energy dissipation flux (DI 0 /RC) values were observed. Regardless of the phenological stage, the presence of F. equiseti in the roots of cotton plants caused high transpiratory rates in the plants, suggesting non-stomatic water loss and photochemical damage. In contrast, non-inoculated plants produced more photosynthetic pigments and showed higher WUE and photochemical efficiency, as indicated by the high PI ABS values. Leaf histopathology assessment revealed more fragile regions of the epidermis, such as the contact region between the guard cells and adjacent epidermal cells, as well as the basal region of glandular trichomes as important access routes for F. equiseti to the inner leaf layers at all developmental stages. This study confirmed that the root colonization of cotton plants with F. equiseti can more intensely impact the physiological quality of the plants, regardless of the developmental stage.

Metabolomic profiling and correlations of supercritical extracts of guarana - Leila Larisa Medeiros Marques; Fabianne Martins Ribeiro; Celso Vataru Nakamura; Ane Stefano Simionato; Galdino Andrade; Acácio Antonio Ferreira Zielinski; Carlos Alexandre Carollo; Denise Brentan da Silva; Admilton Gonçalves de Oliveira; João Carlos Palazzo de Mello (Natural Product Research, 2024)

Copper and silver nanoparticles control coffee rust: decrease the quantity of sprayed active ingredients and is an alternative for sustainable coffee production - Felipe Douglas Soares Leal; Helon Santos Neto; Indiara Carol Lopes Pinheiro; Julia Marques Oliveira; Adélia Aziz Alexandre Pozza; Edson Ampélio Pozza (European Journal of Plant Pathology, 2024)

Blowdown of CO2 vessels at low and medium pressure conditions: Experiments and simulations - Michael Drescher; Adil Fahmi; Didier Jamois; Christophe Proust; Esteban Marques-Riquelme; Jed Belgaroui; Leyla Teberikler; Alexandre Laruelle (Process Safety and Environmental Protection, 2023)

Polymeric Nanocapsules Containing Ozonated Oil and Terbinafine Hydrochloride as a Potential Treatment Against Dermatophytes - Francielli Lima dos Santos; Júlia Capp Zilles; Andressa Urbano Machado; Morgana Souza Marques; Bárbara Souza da Costa; Irene Clemes Kulkamp Guerreiro; Alexandre Meneghello Fuentefria; Renata Vidor Contri (AAPS PharmSciTech, 2023)

Behavioural compensation of extruded urea level and the effects of supplementation presencefor finished lambs in tropical grass pastures - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Luís Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Marina de Nadai Bonin Gomes; Alexandre Menezes Dias; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Neila Lidiany Ribeiro; Antonio Leandro Chaves Gurgel; Gabriela Oliveira de Aquino Monteiro; et al. (Small Ruminant Research, 2023)

Prophylactic and therapeutic effects of a nanocomposite (silver nanoparticle plus Terminalia catappa) against Saprolegnia parasitica in tambaqui - Juliana Oliveira Meneses; Joel Artur Rodrigues Dias; Fernanda dos Santos Cunha; Hugo Leandro dos Santos; Thays Brito Reis Santos; Cindy Caroline Moura Santos; Ricardo Marques Nogueira Filho; Peterson Emmanuel Guimarães Paixão; Natalino da Costa Sousa; Márcia Valéria Silva do Couto; Higo Andrade Abe; Francisco José dos Santos; et al. (Aquaculture, 2023)

d-Limonene complexed with cyclodextrin attenuates cardiac arrhythmias in an experimental model of doxorubicin-induced cardiotoxicity: Possible involvement of calcium/calmodulin-dependent protein kinase type II - Aimée Obolari Durço; Diego Santos Souza; Paula Rhana; Alexandre Dantas Costa; Leisiane Pereira Marques; Lucas Alexandre Barbosa Oliveira Santos; Adriano Antunes de Souza Araujo; Marcus Vinicius de Aragão Batista; Danilo Roman-Campos; Marcio Roberto Viana dos Santos (Toxicology and Applied Pharmacology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Impact of tectonic topographic rejuvenation in landscapes with high bedrock/duricrust strength: Insights from geomorphic evidence in a post-rifted region (SE Brazil) - Daniela Schievano de Campos; Marcilene dos Santos; Karina P.P. Marques; Alexandre Christófaro Silva; Pablo Vidal-Torrado (Geomorphology, 2023)

Myrtle (Eugenia gracillima Kiaersk.) as a fermented alcoholic beverage alternative to wine: Preliminary study - Bruno Fonsêca Feitosa; Regilane Marques Feitosa; Emanuel Neto Alves de Oliveira; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Renato Costa da Silva; Inacia dos Santos Moreira; Natiele Piovesan (Food Bioscience, 2023)

Deontic signs increase control monitoring: evidence from a modified traffic flanker task - Teresa Garcia-Marques; Pedro Figueira; Alexandre Fernandes; João Martins (Cognitive Processing, 2023)
Deontic norms are expected to impose individuals’ control over their behavior. In this paper, we address such norms presented in traffic signs and test their influence over executive control functions. For Experiment 1, we develop a traffic flanker task in which the typical neutral arrows are replaced with traffic prohibition/obligation signs. Experiment 2 isolated the deontic aspect of the signs using simple arrows on red, blue, and green backgrounds and either primed them to be interpreted as traffic signs or as elements of a gaming console controller. Results in both studies show evidence of controlling context interferences more efficiently when dealing with deontic (traffic) signs than with simple arrows (Experiment 1) or with similar perceptive targets when primed with a deontic context than with a gaming context (Experiment 2). In both studies, obligation/blue signs mitigate flanker effects less than prohibition/red signs. Stimuli color affects the alertness of the cognitive system, with the color red being, by itself, a cue for increased control. Based on temporal analysis, we further discuss these results as evidence of an increase in proactive control that aims to prevent the occurrence of undesirable influence.

Nuclear magnetic resonance-based metabolomics in goat ovarian follicular fluid - Irving Mitchell Laines Arcce; Lorena Mara Alexandre Silva; Kirley Marques Canuto; Elenilson de Godoy Alves Filho; Francisco Carlos de Sousa; Luciana Magalhães Melo; Maiana Silva Chaves; Maurício Fraga van Tilburg; Vicente José de Figueirêdo Freitas (Small Ruminant Research, 2023)

Non-self glycan structures as possible modulators of cancer progression: would polysaccharides from Cryptococcus spp. impact this phenomenon? - Israel Diniz-Lima; Leonardo Marques da Fonseca; Jhenifer Santos Dos Reis; Debora Decote-Ricardo; Alexandre Morrot; Jose Osvaldo Previato; Lucia Mendonça Previato; Celio Geraldo Freire-de-Lima; Leonardo Freire-de-Lima (Brazilian Journal of Microbiology, 2023)

Post-feeding Molecular Responses of Cobia (Rachycentron canadum): RNA-Sequencing as a Tool to Evaluate Postprandial Effects in Hepatic Lipid Metabolism - Bruno C. Araújo; David Aciole Barbosa; Renato M. Honji; Giovana S. Branco; Fabiano B. Menegidio; Victor H. Marques; Renata G. Moreira; Marcelo V. Kitahara; Artur N. Rombenso; Paulo H. de Mello; Alexandre W. S. Hilsdorf (Marine Biotechnology, 2023)

Vitamin D3 improves spatial memory and modulates cytokine levels in aged rats - Tatiani Bellettini-Santos; Michelle Lima Garcez; Francielle Mina; Natália Quadros Magnus; Nathalia de Souza Pereira; Ariandne de Oliveira Marques; Gabriela Serafim Keller; Gabriel Casagrande Zabot; Natália Baltazar do Nascimento; Eduarda Behenck Medeiros; Lisienny Campoli Tono Rempel; Ewa Kucharska; et al. (Metabolic Brain Disease, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Preserved interactions between acid and intermediate magmas in a 2.15–2.10 Ga Rhyacian continental arc: Insights from petrographic, geochemical and isotopic data of the Macuco de Minas metagranitoid, Mineiro belt, Brazil - Charlys Vaz de Sant'Anna Neves; Ciro Alexandre Ávila; Everton Marques Bongiolo; Reiner Neumann; Wilson Teixeira; Fabiano Richard Leite Faulstich; Mônica Heilbron; Mauro César Geraldes; Cláudio de Morisson Valeriano (Lithos, 2023)

Dating hydrothermal processes related to the formation of the Lagoa Real uranium deposits using in situ U–Pb dating of andradite and titanite - Camila Marques; Kathryn A. Cutts; Alexandre Raphael Cabral; Cristiano Lana; Francisco Javier Rios; Ian Buick (Journal of South American Earth Sciences, 2023)

Potential in vitro action of an adenosine analog and synergism with penicillin against Corynebacterium pseudotuberculosis - Pedro Negri Bernardino; Carolina Lechinski de Paula; Ana Flávia Marques Pereira; Márcio Garcia Ribeiro; Vasco Ariston de Carvalho Azevedo; Alexandre Secorun Borges; Ary Fernandes-Júnior; José Paes Oliveira-Filho (Brazilian Journal of Microbiology, 2023)

Correction to: Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Expression of O-glycosylated oncofetal fibronectin in alternatively activated human macrophages - Marcos Andre Rodrigues da Costa Santos; Jhenifer Santos dos Reis; Carlos Antonio do Nascimento Santos; Kelli Monteiro da Costa; Pedro Marçal Barcelos; Karen Queiroz de Oliveira Francisco; Pedro Antônio Guimarães Notaroberto Barbosa; Emanuelle Damasceno Souza da Silva; Celio Geraldo Freire-de-Lima; Alexandre Morrot; Debora Decote-Ricardo; Israel Diniz-Lima; et al. (Immunologic Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Technologies used in ruminant grazing management: an integrative review - Carolina Marques Costa; Gelson dos Santos Difante; Andrey William Alce Miyake; Antonio Leandro Chaves Gurgel; Juliana Caroline Santos Santana; Camila Celeste Brandão Ferreira Ítavo; Luís Carlos Vinhas Ítavo; Alexandre Menezes Dias; Marcos Antonio Ferreira Júnior (Tropical Animal Health and Production, 2022)

Influence of Sugarcane Variety on Rhizosphere Microbiota Under Irrigated and Water-Limiting Conditions - Leticia B. Pereira; Victor Marques de Oliveira Gambarini; Alexandre Barretto de Menezes; Laura M. M. Ottoboni; Renato Vicentini (Current Microbiology, 2022)

New record of the bat falcon (Falco rufigularis) in northeastern Brazil: Implications for its future distribution under climate change - Maria Eduarda Alves Ferreira; Rodrigo Ferraz Jardim Marques; Hélio Francisco Leite; Alexandre M. Fernandes (Biologia, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Prevalence, distribution and environmental effects on faecal indicator bacteria and pathogens of concern in commercial shellfish production areas in a subtropical region of a developing country (Santa Catarina, Brazil) - Robson Ventura de Souza; Vanessa Moresco; Marilia Miotto; Doris Sobral Marques Souza; Carlos José Alexandre de Campos (Environmental Monitoring and Assessment, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Optimization of Ozonation Process to Remove Psychoactive Drugs from Two Municipal Wastewater Treatment Plants - Deivisson L. Cunha; Alexandre S. A. da Silva; Rodrigo Coutinho; Marcia Marques (Water, Air, & Soil Pollution, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Dereplication and evaluation of the antinociceptive and anti-inflammatory activity of hydroethanolic extract of leaves from Campomanesia xanthocarpa O. Berg - Fabrício Damasceno Leandro; Layla Dutra Marinho Cabral; Tallita Marques Machado; Hector Henrique Ferreira Koolen; Felipe Moura Araújo da Silva; Fernanda Guilhon-Simplicio; Marcelo Aparecido da Silva; Alexandre Giusti-Paiva; Clarice de Carvalho Veloso Moura; Geraldo Alves da Silva (Natural Product Research, 2021)

Benzophenone and Diethyl Phthalate Removal from Real Wastewater by a Multi-stage Hybrid Reactor - Amanda F. do Amaral; Alexandre S. A. da Silva; Rodrigo Coutinho; Deivisson L. Cunha; Marcia Marques (Water, Air, & Soil Pollution, 2021)

Evaluation of caridean ecological distribution in the Ubatuba region, southeastern Brazilian coast using unsupervised machine learning technique - Alexandre Oliveira Marques; Aline Nonato de Sousa; Veronica Pereira Bernardes; Camila Hipolito Bernardo; Danielle Monique Reis; Amanda Thaís Godoy; Adilson Fransozo (Marine Ecology, 2021)
We used the unsupervised machine learning technique to evaluate the environmental factors responsible for modulating the spatial and seasonal distribution of caridean shrimps from a southeastern region of the Brazilian coast. Samplings were collected from seven transects with an artisanal shrimp fishery boat with two double‐rig nets. Samplings occurred every month from October 2008 to September 2009. The most frequently captured species were Exhippolysmata oplophoroides , Leander paulensis, and Nematopalaemon schmitti . The highest abundance of shrimps occurred in autumn at the II, III, and V transects, which present a higher amount of coarse sediment and biodetritic fragments on the bottom. During autumn, the temperatures were the highest and salinity values were the lowest. Data evaluation indicated efficiency in the visualization of interactions of different shrimp species and environmental data. This kind of sediment may be allowing shrimps to burrow in shelters that prevent predation. The seasons with high temperatures and low salinities can offer better conditions for the establishment of the studied species, despite the fact that there is no hypothesis to prove it. Additionally, the higher abundance of such shrimps coincides with vegetal debris deposition, which could serve as food and provide protection for these shrimps. In this region, the vegetation matter deposited at the bottom of the bay comes from the Atlantic Forest. Overall, the preservation of the coastal forest strongly influences the abundance of this taxon, as it provides protection and food for these shrimps.

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity - Edson Fiedler Abreu; Diego Marques Henriques Jung; Alexandre Uarth Christoff; Victor Hugo Valiati; Sharon A. Jansa; Alexandre Reis Percequillo (Systematics and Biodiversity, 2021)

Nitrogen Stocks in Soil Classes Under Different Land Uses in the Brazilian Semiarid Region - Uemeson José dos Santos; Everardo Valadares de Sá Barretto Sampaio; Eunice Maia de Andrade; Alexandre de Siqueira Pinto; Bruno de Oliveira Dias; Kennedy Nascimento de Jesus; Mônica da Silva Santana; Tiago Diniz Althoff; Milton Marques Fernandes; Rômulo Simões Cezar Menezes (Journal of Soil Science and Plant Nutrition, 2021)

Wavelength and light intensity enhance growth, phytochemical contents and antioxidant activity in micropropagated plantlets of Urtica dioica L. - Adriane Duarte Coelho; Camila Knopp de Souza; Suzan Kelly Vilela Bertolucci; Alexandre Alves de Carvalho; Gustavo Costa Santos; Thainá de Oliveira; Erica Alves Marques; Juliana Pace Salimena; José Eduardo Brasil Pereira Pinto (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

AMPAr GluA1 Phosphorylation at Serine 845 in Limbic System Is Associated with Cardiac Autonomic Tone - Hiago Murilo Melo; Cristiane Ribeiro de Carvalho; Alexandre Ademar Hoeller; Jefferson Luiz Brum Marques; Marcelo Neves Linhares; Mark William Lopes; Guilherme Loureiro Fialho; Peter Wolf; Katia Lin; Zuner A. Bortolotto; Jeremy M. Henley; André D’Ávila; et al. (Molecular Neurobiology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Impact of the Replacement of Wheat Flour by Oat, Amaranth, and Quinoa Flours in Tilapia Balls - Heloisa Teixeira; Carlos Alexandre Ciola; Lucas De Souza Nespeca; Tamires Barlati Vieira da Silva; Evandro Bona; Leila Larisa Medeiros Marques; Adriana Aparecida Droval; Flávia Aparecida Reitz Cardoso; Renata Hernandez Barros Fuchs (Journal of Aquatic Food Product Technology, 2020)

Algrizea Minor Sobral, Faria & Proença (Myrteae, Myrtaceae): chemical composition, antinociceptive, antimicrobial and antioxidant activity of essential oil - Bruno Oliveira de Veras; Yago Queiroz dos Santos; Fernanda Granja da Silva Oliveira; Jackson Roberto Guedes da Silva Almeida; Alexandre Gomes da Silva; Maria Tereza dos Santos Correia; Katharina Marques Diniz; João Ricardhis Saturnino de Oliveira; Vera Lúcia de Menezes Lima; Daniela Maria do Amaral Ferraz Navarro; Júlio César Ribeiro de Oliveira Farias de Aguiar; Maria Betânia Melo de Oliveira; et al. (Natural Product Research, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Assisted phoresy of invertebrates by anurans in tank bromeliads: interspecific relationship - Alan Pedro de Araújo; Alexandre Henrique Carvalho Marques; Alexandre Pereira Dantas; Mauro de Melo Junior; Geraldo Jorge Barbosa de Moura; Moacir Santos Tinoco (Aquatic Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Secondary metabolites that could contribute to the monodominance of Erythrina fusca in the Brazilian Pantanal - Darlene Gris; Amanda Galdi Boaretto; Maria Rita Marques; Geraldo Alves Damasceno-Junior; Carlos Alexandre Carollo (Ecotoxicology, 2019)

Transcriptome analysis of acerola fruit ripening: insights into ascorbate, ethylene, respiration, and softening metabolisms - Clesivan Pereira dos Santos; Mathias Coelho Batista; Kátia Daniella da Cruz Saraiva; André Luiz Maia Roque; Rafael de Souza Miranda; Lorena Mara Alexandre e Silva; Carlos Farley Herbster Moura; Elenilson Godoy Alves Filho; Kirley Marques Canuto; José Hélio Costa (Plant Molecular Biology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Interaction with Pantoea agglomerans Modulates Growth and Melanization of Sporothrix brasiliensis and Sporothrix schenckii - Rodrigo Almeida-Paes; Fábio Brito-Santos; Manoel Marques Evangelista Oliveira; Alexandre Melo Bailão; Clayton Luiz Borges; Glauber Ribeiro de Souza Araújo; Susana Frases; Célia Maria de Almeida Soares; Rosely Maria Zancopé-Oliveira (Mycopathologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

High genetic diversity of noroviruses in children from a community-based study in Rio de Janeiro, Brazil, 2014-2018 - Carina Pacheco Cantelli; Marcelle Figueira Marques da Silva; Tulio Machado Fumian; Denise Cotrim da Cunha; Juliana da Silva Ribeiro de Andrade; Fábio Correia Malta; Sérgio da Silva e Mouta Junior; Alexandre Madi Fialho; Marcia Terezinha Baroni de Moraes; Patricia Brasil; Marize Pereira Miagostovich; José Paulo Gagliardi Leite (Archives of Virology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Correction to: Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Agricultural diversification reduces the survival period of Sclerotinia sclerotiorum sclerotia - Alexandre Dinnys Roese; Gloria Soriano Vidal; Walmes Marques Zeviani; Anibal de Moraes; Louise Larissa May De Mio (European Journal of Plant Pathology, 2018)

Metal contamination levels and biochemical stress responses in the catshark Scyliorhinus canicula off the Portuguese coast - Alexandre Marques; Luís Alves; Marco Lemos; Sara Novais (Frontiers in Marine Science, 2018)

Vitamin D3 Reverses the Hippocampal Cytoskeleton Imbalance But Not Memory Deficits Caused by Ovariectomy in Adult Wistar Rats - Cassiana Siebert; Paula Pierozan; Janaina Kolling; Tiago Marcon dos Santos; Matheus Coimbra Sebotaio; Eduardo Peil Marques; Helena Biasibetti; Aline Longoni; Fernanda Ferreira; Regina Pessoa-Pureur; Carlos Alexandre Netto; Angela T. S. Wyse (NeuroMolecular Medicine, 2017)

Does hydroelectric reservoirs affect the structure of surrounding tree communities? A test of hypotheses in subtropical South America - Leonardo Marques Urruth; Alexandre Fadigas Souza; Juliano Morales Oliveira (Brazilian Journal of Botany, 2017)

Renewable energy and greenhouse gas emissions from the waste sectors of European Union member states: a panel data analysis - Hélde Araujo Domingos; Alexandre Magno De Melo Faria; José Alberto Fuinhas; António Cardoso Marques (Environmental Science and Pollution Research, 2017)

Antarctic strict anaerobic microbiota from Deschampsia antarctica vascular plants rhizosphere reveals high ecology and biotechnology relevance - Rafael José Marques Peixoto; Karla Rodrigues Miranda; Leandro Araujo Lobo; Alessandra Granato; Pedro de Carvalho Maalouf; Hugo Emiliano de Jesus; Caio T. C. C. Rachid; Saulo Roni Moraes; Henrique Fragoso dos Santos; Raquel Silva Peixoto; Alexandre Soares Rosado; Regina Maria Cavalcanti Pilotto Domingues (Extremophiles, 2016)

Barn owl feathers as biomonitors of mercury: sources of variation in sampling procedures - Inês Roque; Rui Lourenço; Ana Marques; João Pedro Coelho; Cláudia Coelho; Eduarda Pereira; João E. Rabaça; Alexandre Roulin (Ecotoxicology, 2016)

Influence of verapamil on the pharmacokinetics of oxcarbazepine and of the enantiomers of its 10-hydroxy metabolite in healthy volunteers - Natalícia de Jesus Antunes; Lauro Wichert-Ana; Eduardo Barbosa Coelho; Oscar Della Pasqua; Veriano Alexandre Junior; Osvaldo Massaiti Takayanagui; Eduardo Tozatto; Maria Paula Marques; Vera Lucia Lanchote (European Journal of Clinical Pharmacology, 2016)

Assessment of Temperature and Predation stress on the Goby (Gobius paganellus) - Paul Nina; Novais Sara; Silva Cátia; Marques Alexandre; Seixas Manuel; Kunzmann Andreas; Lemos Marco (Frontiers in Marine Science, 2016)

Sand smelt ability to cope and recover from CO2-induced ocean acidification stress during early stages assessed through development and biochemical responses - Silva Cátia; Lemos Marco; Lopes Ana; Prasuhn Mareen; Seixas Manuel; Marques Alexandre; Faria Ana; Gonçalves Emanuel; Novais Sara (Frontiers in Marine Science, 2016)

Effects of untreated and treated oilfield-produced water on seed germination, seedling development, and biomass production of sunflower (Helianthus annuus L.) - Mônica Regina da Costa Marques; Paulo Sérgio Alves de Souza; Michelle Machado Rigo; Alexandre Andrade Cerqueira; Julieta L. de Paiva; Fábio Merçon; Daniel Vidal Perez (Environmental Science and Pollution Research, 2015)

How much do we know about the endangered Atlantic Forest? Reviewing nearly 70 years of information on tree community surveys - Renato A. F. de Lima; Danilo P. Mori; Gregory Pitta; Melina O. Melito; Carolina Bello; Luiz F. Magnago; Victor P. Zwiener; Daniel D. Saraiva; Márcia C. M. Marques; Alexandre A. de Oliveira; Paulo I. Prado (Biodiversity and Conservation, 2015)

Advanced Oxidation Treatment of Recalcitrant Wastewater from a Wood-Based Industry: a Comparative Study of O3 and O3/UV - Henrik Hansson; Fabio Kaczala; Alexandre Amaro; Marcia Marques; William Hogland (Water, Air, & Soil Pollution, 2015)

Exogenously induced brain activation regulates neuronal activity by top-down modulation: conceptualized model for electrical brain stimulation - Lauren Naomi Spezia Adachi; Alexandre Silva Quevedo; Andressa de Souza; Vanessa Leal Scarabelot; Joanna Ripoll Rozisky; Carla de Oliveira; Paulo Ricardo Marques Filho; Liciane Fernandes Medeiros; Felipe Fregni; Wolnei Caumo; Iraci L. S. Torres (Experimental Brain Research, 2015)

Germline CDKN2A mutations in Brazilian patients of hereditary cutaneous melanoma - Alexandre Leon Ribeiro de Ávila; Ana Cristina Victorino Krepischi; Luciana Facure Moredo; Talita Ferreira Marques Aguiar; Felipe Carneiro da Silva; Bianca Costa Soares de Sá; Amanda França de Nóbrega; Maria Isabel Waddington Achatz; João Pedreira Duprat; Gilles Landman; Dirce Maria Carraro (Familial Cancer, 2014)

Sponges as substrata and early life history of the tubulariid Zyzzyzus warreni (Cnidaria: Hydrozoa) in the São Sebastião Channel, Brazil - Carlos José Alexandre De Campos; Alvaro Esteves Migotto; Ulisses Pinheiro; Antonio Carlos Marques (Marine Biology Research, 2012)

Histopathology of black spot symptoms in sweet oranges - João Paulo Rodrigues Marques; Marcel Bellato Spósito; Alexandre Furtado Silveira Mello; Lilian Amorim; Matheus Mondin; Beatriz Appezzato-da-Glória (European Journal of Plant Pathology, 2012)

High frequency of BF mosaic genomes among HIV-1-infected children from Sao Paulo, Brazil - Cristina Mendes de Oliveira; Flávia Jacqueline Almeida; Rosangela Rodrigues; Marcia Crozatti; Carla Maria Pasquareli Vazquez; Maria do Socorro Carneiro Ferrão; Alexandre Ely Campeas; Silvia Regina Marques; Eitan Naaman Berezin; Luis Fernando de Macedo Brígido (Archives of Virology, 2008)

Antioxidant activities of sulfated polysaccharides from brown and red seaweeds - Micheline Cristiane Rocha de Souza; Cybelle Teixeira Marques; Celina Maria Guerra Dore; Fernando Roberto Ferreira da Silva; Hugo Alexandre Oliveira Rocha; Edda Lisboa Leite (Journal of Applied Phycology, 2007)

Spatial Variability of Irrigated Corn Yield in Relation to Field Topography and Soil Chemical Characteristics - J. R. Marques Da Silva; C. Alexandre (Precision Agriculture, 2005)

Competition for feeding in waders: a case study in an estuary of south temperate Europe (Mondego, Portugal) - Tiago Múrias Santos; João Alexandre Cabral; Ricardo Jorge Lopes; Miguel Pardal; João Carlos Marques; John Goss-Custard (Hydrobiologia, 2005)

Brazil's Electric Power Choices and Their Corresponding Carbon Emissions Implications - Roberto Schaeffer; Jeffrey Logan; Alexandre Salem Szklo; William Chandler; João Carlos de Souza Marques (Mitigation and Adaptation Strategies for Global Change, 2001)